Formation of atmospheric molecular clusters of methanesulfonic acid–Diethylamine complex and its atmospheric significance. (1st April 2020) - Xu, Cai-Xin; Jiang, Shuai; Liu, Yi-Rong; Feng, Ya-Juan; Wang, Zi-Hang; Huang, Teng; Zhao, Yu; Li, Jie; Huang, Wei
Abstract: Field observations in a marine atmospheric environment imply the occurrence of significant concentrations of dimethylamine (DMA) and diethylamine (DEA) as well as methanesulfonic acid (MSA) in particulate formation. Among these particulates, studies on the interaction of MSA with DMA are well known; however, fundamental studies relating to the environmental impact of DEA on aerosol formation and its nucleation ability relative to the known ones are lacking. In this research, quantum chemical calculations and cluster kinetic modeling were used to analyze the aerosol formation potential of the reaction of DEA with MSA. Structural and thermodynamic evidence demonstrate a strong clustering stability in the processes of new particle formation (NPF). Driven by proton transfer, the clusters exhibit a low free-energy barrier distributed along the diagonal. The results of cluster kinetic analysis indicate that the aerosol formation potential of the MSA-DEA system at the parts per trillion (ppt) level is inferior to that of sulfuric acid (SA)–DMA, and slightly superior to that of SA–methylamine (MA) but far superior to that of MSA–DMA, implying a relatively strong nucleation capability for MSA-DEA system. This result implies that the MSA-DEA system plays a potentially significant role in NPF in the marine environment. Highlights: A possible role in new particle formation in the marine atmosphere. MSA-DEA clusters with a similar number of acids and amines are more stable. Proton transfer enhances the stability of MSA–DEA clusters. MSA is more strongly bound in MSA-DEA clusters than DEA.